Manual de recreación al aire libre como medio para fomentar el turismo de la Parroquia Alóag, Cantón Mejía, Provincia de Pichincha en el año 2015. - Sandoval Chanco, Jorge Ramiro (2015)
The development of this work is focused on the realization of outdoor recreational activities which encompasses all actions related to the enjoyment and personal satisfaction. However, the outdoor recreation used as a means to boost tourism has not been very depth among the inhabitants of the parish, as well as their knowledge of the benefits are unknown to the vast majority of the community. Therefore, they have not practiced this type of recreation that promotes tourism, which is why the main objective of the work is to research and to provide a manual of recreational activities to promote tourism in places that have tourist places and in turn generate in participants with a healthy lifestyle eradicating sedentary lifestyle and obesity. For the preparation of this research work the descriptive research and non-experimental descriptive method is used, through interview techniques and survey applied to residents and teachers where it was found that the issue of outdoor recreation to promote tourism is little known in the environment you see this theme seeks to provide future researchers a learning resource, the proposed work furnish to the inhabitants promote tourism through outdoor recreational activities that is central to their lifestyle thus research priority becomes important in Physical Culture.